Factors Favouring the Resurgence of Cases of Malaria in The Populations of The Provinces of Maniema and Kwango in the Democratic Republic of Congo - Priss, Tambwe Mwabi; Bonny, Assani Wakenge; Alphonse, Masandi Milondo; John, Kahozi Mihali; Désiré, Kibonge Pascal; Jeanne d’Arc, Iragi Mundinga; Placide, Mbungi Pangalala (British Journal of Healthcare and Medical Research, 2024)
Malaria remains one of the most widespread and deadly parasitic diseases in the world and is a real public health problem. The aim of this study was to analyse the factors favouring the resurgence of malaria cases in the provinces of Maniema and Kwango. It was a case-control study based on a retrospective survey of people of both sexes hospitalised (or on sick call) for severe malaria, with data collection covering a 12-month period from 2021-2022. Factors favouring the resurgence of malaria cases were determined by multivariate analysis using logistic regression. The present study showed that actions taken to reduce malaria in the community (OR: 0.313; p=0.000), participation in a sanitation activity (OR: 0.687; p=0.041) and socio-economic level (OR: 0.629; p=0.000) were factors favouring the resurgence of malaria cases.